The effect of pasture biostimulant treatment and decreased concentrate supplementation on pasture production and the production and profitability of pasture fed lactating Jersey cows - De Beer, Janika (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.